Estimates of incidence, prevalence, mortality, and disability‐adjusted life years of lung cancer in Iran, 1990–2019: A systematic analysis from the global burden of disease study 2019. (13th June 2022) - Shokri Varniab, Zahra; Sharifnejad Tehrani, Yeganeh; Pourabhari Langroudi, Ashkan; Azadnajafabad, Sina; Rezaei, Negar; Rashidi, Mohammad‐Mahdi; Esfahani, Zahra; Malekpour, Mohammad‐Reza; Ghasemi, Erfan; Ghamari, Azin; Dilmaghani‐Marand, Arezou; Mohammadi Fateh, Sahar; et al.
Abstract: Background: Lung cancer is one of the leading cancers, with a high burden worldwide. As a developing country, Iran is facing with population growth, widespread tobacco use, demographic and epidemiologic changes, and environmental exposures, which lead to cancers becoming a severe concern of public health in Iran. We aimed to examine the burden of lung cancer and its risk factors in Iran. Methods: We utilized the Global Burden of Disease 2019 data and analyzed the total burden of the lung cancer and seven related risk factors by sex, age at national and sub‐national levels from 1990 to 2019. Results: The lung cancer age‐standardized death rate increased from 11.8 (95% Uncertainty Interval: 9.7–14.4) to 12.9 (11.9–13.9) per 100, 000 between 1990 and 2019. This increase was among women from 5 (4.2–7.1) to 8 (7.2–8.8) per 100, 000; in contrast, there was a decline among men from 18.5 (14.8–22.6) to 17.8 (16.2–19.4) per 100, 000. The burden of lung cancer is concentrated in the advanced age groups. Smoking with 53.5% of total attributable deaths (51.0%–55.9%) was the leading risk factor. At the provincial level, there was a wide range between the lowest and highest, from 8.3 (7.0–10.0) to 19.1 (16.4–22.0) per 100, 000 population in the incidence rate and from 8.7 (7.3–10.3) to 20.6 (17.7–24.0) per 100, 000 population in mortality rate, respectively in Tehran and West Azerbaijan provinces in 2019. Conclusion: The increasing trend of lung cancer burden among the entire Iranian population, the inter‐provincial disparities, and the significant rise in burden of this cancer in women necessitate the urgent implementation and development of policies to prevent and manage lung cancer burden and strategies to reduce exposure to risk factors. Abstract : Age‐standardized incidence, DALYs, and death rate in females were lower than males but had a remarkable increase. The study showed that the highest incidence and DALYs rate of LC were in the age group >70. Smoking was the first leading risk factor among the overall population, men, and all provinces of Iran.